Penegakan Hukum Terhadap Pelaku Cyber Bullying di Kepolisian Daerah Bali pada Masa Pandemi Covid-19 - Ni Komang Putri Pratiwi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
Based on observations at the hotel in the Sanur area, there were several foreign workers working at the hotel before the permit was approved. This study aims to examine the implementation of the provisions on the use of foreign workers and examine the obstacles in implementing the provisions on the use of foreign workers at hotels in the Sanur area. This research method is empirical legal research with a statutory approach. There are two sources of data used, namely primary and secondary legal materials. To obtain valid data, the researchers used observation and interview techniques. Research data that has been collected, processed and analyzed qualitatively descriptive. The results show that special requirements such as foreign workers must have specific skills, companies that guarantee foreign workers must have a permit to employ foreign workers and foreign workers must meet immigration requirements such as passports, visas and KITAS. The use of foreign workers in hotels in the Sanur area of ​​Denpasar City is quite good, but there are obstacles in implementing the provisions for the use of foreign workers in hotels in the Sanur area when foreign workers are needed urgently so that they take a shortcut by extending a Visit Visa when the work visa has expired. The suggestion is that companies in Indonesia should prioritize competent local workers and follow the rules regarding the use of foreign workers.